HOW DO MINERAL COATINGS AFFECT DISSOLUTION RATES? AN EXPERIMENTAL STUDY OF COUPLED CACO3 DISSOLUTION - CDCO3 PRECIPITATION - Cubillas P.; Köhler S.; Prieto M.; Causserand C.; Oelkers E.H. (My University, 2005)
Coupled CaCO3 dissolution-otavite (CdCO3) precipitation experiments have been performed to 1) quantify the effect of mineral coatings on dissolution rates, and 2) to explore the possible application of this coupled process to the remediation of polluted waters. All experiments were performed at 25°C in mixed-flow reactors. Various CaCO3 solids were used in the experiments including calcite, aragonite, and ground clam, mussel, and cockle shells. Precipitation was induced by the presence of Cd(NO3)2 in the inlet solution, which combined with aqueous carbonate liberated by CaCO3 dissolution to supersaturate otavite. The precipitation of an otavite layer of less than 0.01 μm in thickness on calcite surfaces decreases its dissolution rate by close to two orders of magnitude. This decrease in calcite dissolution rates lowers aqueous carbonate concentrations in the reactor such that the mixed-flow reactor experiments attain a steady-state where the reactive fluid is approximately in equilibrium with otavite, arresting its precipitation. In contrast, otavite coatings are far less efficient in lowering aragonite, and ground clam, mussel, and cockle shell dissolution rates, which are comprised primarily of aragonite. A steady-state is only attained after the precipitation of an otavite layer of 3–10 μm thick; the steady state CaCO3 dissolution rate is 1–2 orders of magnitude lower than that in the absence of otavite coatings. The difference in behavior is interpreted to stem from the relative crystallographic structures of the dissolving and precipitating minerals. As otavite is isostructural with respect to calcite, it precipitates by epitaxial growth directly on the calcite, efficiently slowing dissolution. In contrast, otavite’s structure is appreciably different from that of aragonite. Thus, it will precipitate by random three dimensional heterogeneous nucleation, leaving some pore space at the otavite-aragonite interface. This pore space allows aragonite dissolution to continue relatively unaffected by thin layers of precipitated otavite. Due to the inefficiency of otavite coatings to slow aragonite and ground aragonite shell dissolution, aragonite appears to be a far better Cd scavenging material for cleaning polluted waste waters.